Processes of heat and mass transfer in gas and heat protective suit with ice-water cold-storage accumulators - Гаврилко, О. А.; Білінський, Б. О.; Дендаренко, Ю. Ю.; Havrylko, A.; Bilinskiy, B.; Dendarenko, Y. (Видавництво Львівської політехніки, 2018)
Наведено математичну модель процесів тепломасоперенесення в системі „навколишнє середовище–захисний одяг–людина”, що враховує одночасне проникнення з навколишнього середовища теплоти і отруйних хімічних речовин до багатошарової оболонки одягу з повітряними прошарками, на підставі результатів якої обґрунтовано параметри газотеплозахисного костюму. Це зумовлено тим, що під час ведення аварійно-рятувальних робіт підрозділами пожежо-рятувальної і гірничорятувальної служб на підприємствах вугільної, хімічної, нафтопереробної та металургійної промисловостей народного господарства виникають несприятливі мікрокліматичні умови (висока температура, вологість повітря, задимленість, загазованість довкілля). Так, під час пожежогасіння або ведення гірничорятувальних робіт виникали ситуації, коли до шахт проникали отруйні хімічні речовини: хлорбензол, ацетон, бензол, сірчана кислота тощо. У результаті багато пожежників-рятувальників або гірничорятувальників отримували отруєння і теплові ураження (температура повітря сягала понад 40 °С), причому використання рятувальниками кращих у світовій практиці газозахисних костюмів виявилося неефективним.

The article dwells on the mathematical model of heat and mass transfer processes in „environment-protective clothing-human” system which takes into account simultaneous penetration of ambient heat and toxic chemicals in the multi-layer membrane of garments with air gap. On the basis of this model, the parameters of a gas and heat protective suit are reasonably defined. This is due to the fact that during emergency and rescue operations units of the fire and rescue service and mining and rescue services at the enterprises of the coal, chemical, oil refining and metallurgical industries of the national economy there are unfavorable microclimatic conditions (high temperature, humidity of air, smoothness, gas pollution of the environment). So, in the case of firefighting or mine-rescue operations, there were situations when poisonous chemicals entered into fires or mines: chlorobenzene, acetone, benzene, sulfuric acid, and others. As a result, many firefighters or rescuers received poisoning and thermal damage (air temperature reached 40 °C), with the use of rescuers of the best in the world of gas-protective suits proved to be ineffective. In this regard, there was the necessity in developing a gas and heat protective suit with the multi-layered membrane and with the use of ice-water cold-storage elements (CE) which are used by mine rescuers in heat protective clothing. In addition, according to the requirements of the State Militarized Mine Rescuing Service of Ukraine, the duration of works, conducted by a rescuer in a suit with the minimal mass and under 40 ºС temperature, has to constitute not less than 120 minutes. When a rescuer is under the influence of the most toxic substance (chlorobenzene when its concentration in outputs is 15 g/m3), the duration of operations has to be 180 min. Objective of the research is to develop the mathematical model of nonstationary processes of heat and mass transfer in “environment – protective clothing – human” system, and on the basis of it to define parameters of a gas and heat protective suit which would ensure safe work under the above-mentioned conditions. To develop a mathematical model of heat transfer in the system “the environment – protective clothing – a person” we accept the design scheme of the shell of a suit, which is subject to thermal and chemical effects from the environment and the thermal – the human body.
Процеси тепломасоперенесення у газотеплозахисному костюмі з водольодяними акумуляторами холоду
Keywords: математична модель; температура; отруйні речовини; газотеплозахисний костюм; тепломасоперенесення; охолоджувальні елементи; підодяговий простір; інтенсивність теплообміну; кількість елементів; mathematical model; temperature; toxic substances; gas and heat protective suit; heat and mass transfer; cooling elements; space under the suit; intensity of heat exchange; number of elements; 622.867; 623.455.1